Penentuan Tingkat Efisiensi Komposisi H3po4 pada Proses Degumming dalam Pembuatan Pure Plant Oil dari Crude Palm Oil off-Grade - Dany Almay Arsanto; Darmawan Wahyu Pratama; SD Sumbogo Murti; Sintha Soraya; Widya Widya (Jurnal Indonesia Sosial Teknologi, 2022)
Pure Plant Oil (PPO) is oil obtained directly from pressing or pressing oil seeds, purified oil, or crude oil without involving chemical modification. The purpose of this study was to determine the quality of PPO as an alternative fuel to substitute for HSD (High Speed ​​Diesel). This study uses the Do Of Experiment (DOE) method which consists of two treatments, namely before degumming and after degumming. Degumming process is carried out using H3PO4 for latex separation. Neutralization process is carried out with NaOH solution to separate free fatty acids from oil or fat, by reacting free fatty acids with bases or other reagents to form soap (soap stock). The conditions carried out in the Degumming and Neutralization Process are Concentration (20%, 30% and 40%), and Volume (20 ml, 30 ml and 40 ml). The calorific value and flash point were used as test parameters for PPO products. The most effective amount of H3PO4 for use as a reagent during the degumming process is 0.3, where a concentration of 40% H3PO4 as much as 20 ml is able to bind Gum to Off-Grade CPO as much as 6 ml. The calorific value of CPO tested using a bomb calorimeter is 9,778 Cal/g and the flash point of PPO in accordance with ASTM D 92 is 287 oC, and is in accordance with the quality standard of Pure Vegetable Oil (PPO) as stipulated in SNI, Number 73/KEP/BSN/ 2/2006.